Reaksi Pasar Modal Indonesia Sebelum dan Sesudah Pengumuman Kebijakan Pemerintah Tentang Status Darurat Bencana Covid-19 - Komang Endri Agustiawan; Edy Sujana (Universitas Pendidikan Ganesha, 2020)
This research is an event study research with the aim of examining the information content of the event of the announcement of government policies regarding the emergency status of the Covid-19 disaster, using an indicator of the difference in the average abnormal return and trading volume activity before and after the announcement event. The population used is the member companies of the LQ45 index, and the sampling method was purposive sampling, in order to obtain a sample of 45 companies. The measurement period is carried out 5 days before the announcement and 5 days after the announcement, and the data used is in the form of secondary data, namely daily stock closing prices, daily LQ45 index, daily share transaction volume, and the number of outstanding company shares. Hypothesis testing uses the paired sample t-test for data that is normally distributed, and the Wilcoxon signed rank test for data that is not normally distributed. The results obtained are that there is no significant difference in the average abnormal return and trading volume activity of LQ45 stocks in the period before and after the announcement of government policy regarding the emergency status of the Covid-19 disaster.